2004
DOI: 10.1002/jsfa.1918
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of carotenoids in ripe jackfruit (Artocarpus heterophyllus) kernel and study of their bioconversion in rats

Abstract: Vitamin A deficiency is of public health importance in Sri Lanka. Carotenoids are a significant source of provitamin A. The objective of this study was to analyse the carotenoid composition of jackfruit (Artocarpus heterophyllus sinhala: Waraka) kernel using MPLC and visible spectrophotometry and to determine the bioavailability and bioconversion of carotenoids present in jackfruit kernel by monitoring (i) the growth and (ii) levels of retinol and carotenoids in the liver and serum of Wistar rats provided with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
4
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 7 publications
(6 reference statements)
4
31
4
3
Order By: Relevance
“…However, in these works, the above described minimum criteria were not fulfilled and the carotenoid identification was solely based on the elution order on the chromatographic system, UV-visible spectra characteristics and sometimes chemical reactions. This identification procedure resulted on the identification of crocetin, among other carotenoids, in jackfruit [14]. However, up to now, crocetin and its derivatives were only found in saffron and gardenia [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in these works, the above described minimum criteria were not fulfilled and the carotenoid identification was solely based on the elution order on the chromatographic system, UV-visible spectra characteristics and sometimes chemical reactions. This identification procedure resulted on the identification of crocetin, among other carotenoids, in jackfruit [14]. However, up to now, crocetin and its derivatives were only found in saffron and gardenia [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…According to a literature search, the major carotenoids from jackfruit were determined by open column or high performance liquid chromatography (HPLC) [12][13][14]. However, in these works, the above described minimum criteria were not fulfilled and the carotenoid identification was solely based on the elution order on the chromatographic system, UV-visible spectra characteristics and sometimes chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Results show that these residues could be a significant source of vitamin A in both conventional foods and dietary supplements. People with high dietary intake of beta-carotene or high blood levels of this nutrient have a reduced risk of various diseases, including cancer and heart diseases (Chandrika et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have examined the free sugar distribution and compositions of fatty acids (Chowdhury, Raman, & Mian, 1997), carbohydrates (Rahman, Nahar, Jabbar, & Mosihuzzaman, 1999), aroma volatiles (Swords, Bobbio, & Hunter, 1978;Rasmussen, 1983;K. Wong, Lim, & L. Wong, 1992;Maia, Andrade, & Zoghbi, 2004), carotenoids and phenolics (Chandrika, Jansz, & Warnasuriya, 2005;Jayasinghe, Rupasinghe, Hara, & Fujimoto, 2006;Faria, Rosso, & Mercadante, 2009) from fruits of different jackfruit varieties, as well as antioxidant capacity and phenol content in jackfruit fruit pulp (Jagtap, Panaskar, & Bapat, 2010). For example, an early study found little changes in fruit total acidity during ripening (Bhatia, Siddapa, & Lal, 1955).…”
Section: Introductionmentioning
confidence: 99%